Implementasi Peraturan Walikota Surabaya Nomor 83 Tahun 2023 Tentang Program Padat Karya di Kecamatan Gubeng Kota Surabaya - Yovita Rahma Nurzelanti; M. Kendry Widiyanto; Dida Rahmadanik (Jurnal Relasi Publik, 2024)
Unemployment is a very serious problem in the economy because it affects a person's life physically and mentally. The government responded to this problem by creating a labor-intensive program. The labor-intensive program is an initiative that aims to empower the community, especially productive poor families. This program is designed to achieve several goals, namely reducing unemployment, alleviating poverty, and increasing people's sources of income through the use of natural resources, technology, and workers. This research aims to evaluate the implementation of community empowerment through labor-intensive programs in Gubeng District. This research was conducted with a qualitative descriptive approach and used George C. Edward III's policy implementation theory. The research results show that the implementation of the labor-intensive program in Gubeng District is in accordance with Surabaya Mayor Regulation Number 83 of 2023. However, there are several obstacles to implementation, namely the lack of public interest in the labor-intensive program. Therefore, it is hoped that the Gubeng District government will be more aggressive in providing information regarding labor-intensive programs via social media with the aim of increasing public interest. The government must also evaluate and carry out direct monitoring in the field in the implementation of labor-intensive programs in Gubeng District.